1985
DOI: 10.1021/bi00347a026
|View full text |Cite
|
Sign up to set email alerts
|

Studies of 6-fluoropyridoxal and 6-fluoropyridoxamine 5'-phosphates in cytosolic aspartate aminotransferase

Abstract: The chemical and spectroscopic properties of 6-fluoropyridoxal 5'-phosphate, of its Schiff base with valine, and of 6-fluoropyridoxamine 5'-phosphate have been investigated. The modified coenzymes have also been combined with the apo form of cytosolic aspartate aminotransferase, and the properties of the resulting enzymes and of their complexes with substrates and inhibitors have been recorded. Although the presence of the 6-fluoro substituent reduces the basicity of the ring nitrogen over 10 000-fold, the mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…The pK a values for the imino nitrogens of 2a and 3 obtained here correspond closer to the apparent pK a values of external aldimines, which are usually [9][10][11][42][43][44] than to those of internal aldimines, which are in order of 6-7. [45][46][47] The electron-withdrawing effect of the imino function affects the ring nitrogen whose pK a decreases to 5.8, a normal value for pyridine derivatives. [48][49][50] One anticipates an even larger drop in the absence of the doubly negatively charged phosphate group.…”
Section: N Chemical Shifts and Geometries Of The Inter-and Intramolecmentioning
confidence: 99%
“…The pK a values for the imino nitrogens of 2a and 3 obtained here correspond closer to the apparent pK a values of external aldimines, which are usually [9][10][11][42][43][44] than to those of internal aldimines, which are in order of 6-7. [45][46][47] The electron-withdrawing effect of the imino function affects the ring nitrogen whose pK a decreases to 5.8, a normal value for pyridine derivatives. [48][49][50] One anticipates an even larger drop in the absence of the doubly negatively charged phosphate group.…”
Section: N Chemical Shifts and Geometries Of The Inter-and Intramolecmentioning
confidence: 99%
“…This affects the electronic environment around fluorine at the 6-position, which is particularly pronounced due to the para location. Extensive literature on modifications of vitamin B 6 suggested that the introduction of electron donating or withdrawing groups at the 4 and 5 positions of the pyridoxol ring could significantly alter the pKa of the 3-phenolic group, and the NMR properties at the 6-position [95,99,100]. From a series of analogs 6-fluoropyridoxamine (6-FPAM) was identified as an enhanced pH indicator (pKa 7.05) [94].…”
Section: Fluorinated Vitamin B6 Derivativesmentioning
confidence: 99%
“…Information on the state of the coenzyme in the holoenzyme has largely been obtained by using u.v.-visible absorption spectroscopy or spectrofluorimetry. Thus the spectroscopic features of vitamin B6 derivatives (Matsushima & Martell, 1967;Metzler et al, 1973;Harris et al, 1974;Scott et al, 1985) and related Schiff bases (Metzler et al, 1980;Donoso et al, 1986;Morozov et al, 1988) have been widely studied.…”
Section: Introductionmentioning
confidence: 99%